(untitled) (Clinics, 2013)
OBJECTIVE: To evaluate the effects of percutaneous coronary intervention and thrombolysis after restoration of spontaneous circulation in cardiac arrest patients with ST-elevation myocardial infarction using meta-analysis. METHODS: We performed a meta-analysis of clinical studies indexed in the PUBMED, MEDLINE and EMBASE databases and published between January 1995 and October 2012. In addition, we compared the hospital discharge and neurological recovery rates between the patients who received percutaneous coronary intervention and those who received thrombolysis. RESULTS: Twenty-four studies evaluating the effects of percutaneous coronary intervention or thrombolysis after restoration of spontaneous circulation in cardiac arrest patients with ST-elevation myocardial infarction were included. Seventeen of the 24 studies were used in this meta-analysis. All studies were used to compare percutaneous coronary intervention and thrombolysis. The meta-analysis showed that the rate of hospital discharge improved with both percutaneous coronary intervention (p